2018
DOI: 10.1021/acs.langmuir.8b02729
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical and Thermal Strength in Mixed-Enantiomers-Based Supramolecular Gel

Abstract: Mixing supramolecular gels based on enantiomers leads to re-arrangement of gel fibers at the molecular level, which results in more favorable packing and tunable properties. Bis(urea) compounds tagged with a phenylalanine methyl ester in racemic and enantiopure forms were synthesized. Both enantiopure and racemate compounds formed gels in a wide range of solvents and the racemate (1-rac) formed a stronger gel network compared with the enantiomers. The gel (1R+1S) obtained by mixing equimolar amount of enantiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 95 publications
(157 reference statements)
1
31
1
Order By: Relevance
“…Domodaran et al. investigated the gelation abilities of bis‐urea compounds with two chiral centers [109] . The trend in this study is different from that of Yamanakas’ results, and all homochiral, heterochiral, and racemic bis‐ureas show gelation ability.…”
Section: Urea–urea Intermolecular Hydrogen Bondingcontrasting
confidence: 66%
“…Domodaran et al. investigated the gelation abilities of bis‐urea compounds with two chiral centers [109] . The trend in this study is different from that of Yamanakas’ results, and all homochiral, heterochiral, and racemic bis‐ureas show gelation ability.…”
Section: Urea–urea Intermolecular Hydrogen Bondingcontrasting
confidence: 66%
“…Marchesan et al showed that changing the chirality in the N-terminus of a tripeptide could result in a non-gelator becoming a gelator, with for example VFF becoming a gelator when the d -isomer of the terminal valine was used 13,14. In rare examples, a mixture of two enantiomers has been shown to lead to gels with improved properties 9,15,16…”
Section: Introductionmentioning
confidence: 99%
“…While many of them form gels (not always identical in characteristics) regardless of the enantiomeric composition, relatively simple compounds of this class exhibited their specific properties only in the enantiopure form and did not exhibit in the racemic form, and vice versa. Examples of such behavior are given in reviews [22,23] and this effect has also been noted in recent publications [24][25][26][27]. Subsequently, this minor mystery of chiral gels was obscured by other, significant in meaning and spectacular in illustrations, problems of supramolecular chirality [28,29] and chiral recognition [30], which are clearly manifested in nanostructured media.…”
Section: Introductionmentioning
confidence: 70%